Pengaruh Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan (Studi di PT. ASIA HEALTH ENERGI BEVERAGES SUKABUMI) - Buci Morisson Morisson (KarismaPro, 2020)
Based on multiple regression analysis obtained by linear regression equation Y = 13,531 + 0,321X1 + 0,420X2 + e. Stating that the effect of increasing the value of the leadership unit by 0.321 then the value of employee performance will increase by 32.1%. If work motivation has an additional value of 0.420, the employee's performance value will also increase by 42,0%. Based on the calculation of the coefficient of determination obtained Adjusted (R square) value of 0.446 or 44.6% and the remaining 55.4% is influenced by variables not examined. Based on the calculation of the correlation coefficient, the value is 0.681, the coefficient is at an interval of 0.60 - 0.799, included in the level of "strong" relationship, which means leadership and work motivation have a strong correlation on employee performance. This research is also supported by t-test hypothesis testing, leadership significance value 3,448 2,091 and work motivation 4,336 2,091 resulting in H0 rejected and H1 accepted, which means that leadership and work motivation significantly influence employee performance.